PANEL BETON BERTULANGAN BAMBU SEBAGAI ALTERNATIF BAHAN KONSTRUKSI - Maricar, Shyama; Hasan, Hajatni; Chauf, Kusnindar Abd. (MEKTEK, 2012)
The use of natural materials for construction purposes should be developed. Special reinforced concrete construction, in some cases, the compressive strength is not a determining factor, but rather ductility. On the other hand, bamboo is a natural material has a ductile properties sufficient to be used as reinforcement. For this type of bamboo lear, some properties that are important to note is the compressive strength , σ//= 39.89 MPa, σ┴ = 5.55 MPa, Shear strength is 7.644 MPa and tensile strength is 207.523 MPa. In addition, the physical properties of mortar material used is weight of contents of cement is 1.25 gr/cm3, weigtht ofcontent of sand is 1.60 gr/cm3.From the test results it can be concluded that the test samples for concrete mix bamboo panel with division 1 cement and 4 sand did not change significantly so that the maximum load obtained for testing age from 7 days to 21 days also resulted in maximum load that is not much different. Thus the utilization of bamboo reinforced concrete panels for the purpose of the wall can be done, although it still requires further development.